2011
DOI: 10.1088/0965-0393/19/7/074009
|View full text |Cite
|
Sign up to set email alerts
|

Cohesive zone model for intergranular slow crack growth in ceramics: influence of the process and the microstructure

Abstract: Ceramic polycrystals are prone to slow crack growth (SCG) which is stress and environmentally assisted, similarly to observations reported for silica glasses. The kinetics of fracture are known to be dependent on the load level, the temperature and the relative humidity. In addition, evidence is available on the influence of the microstructure on the SCG rate with an increase in the crack velocity with decreasing the grain size. Crack propagation takes place beyond a load threshold, which is grain size depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…A thermally activated formulation is adopted for the cohesive model which is presented by Romero de la Osa et al. 4,5 It is shown that the formulation can capture the regime I and the load threshold that originates in the a) Corresponding author. lgV K I K I 0 I 0 T, r II III H O 2 Fig.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…A thermally activated formulation is adopted for the cohesive model which is presented by Romero de la Osa et al. 4,5 It is shown that the formulation can capture the regime I and the load threshold that originates in the a) Corresponding author. lgV K I K I 0 I 0 T, r II III H O 2 Fig.…”
mentioning
confidence: 99%
“…The mechanism underlying SCG is described with a cohesive model that represents the reaction-rupture mechanism. A thermally activated formulation is adopted for the cohesive model which is presented by Romero de la Osa et al 4,5 It is shown that the formulation can capture the regime I and the load threshold that originates in the presence of initial stress related to the processing. In this section, a cohesive zone model (CZM) for the reaction-rupture mechanism underlying SCG in single and polycrystal ceramics is presented based on the description of SCG by Michalske and Freiman.…”
mentioning
confidence: 99%
See 3 more Smart Citations